Single incision laparoscopic cystectomy for a huge fimbrial cyst: a rare case report - Bettaiah, Ramesh; Reddy, Chandana A; Gupta, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A case of huge fimbrial cyst is presented, occurring in a 26 year old female. She presented in outpatient department with an incidental diagnosis of a huge cystic mass diagnosed during her routine medical check-up. She was asymptomatic. Ultrasound and CT scan showed an abdominopelvic cystic mass in left adnexa and a right dermoid cyst. Single incision laparoscopic surgery was performed and a huge right fimbrial cyst of 35 cm was noted along with left dermoid cyst. We did bilateral cystectomy through single port laparoscopy. Although there are a few case reports on huge fimbrial cysts which were managed traditionally by laparotomy and recently multiport laparoscopic surgeries, the technique of single incision laparoscopic surgery for proved benign cysts has been described here.